CARMENES – M Dwarfs and their Planets: First Results. Issue Volume 12:Issue S328(2016) (12th September 2017) - Quirrenbach, A.; Amado, P.J.; Ribas, I.; Reiners, A.; Caballero, J.A.; Seifert, W.; Zechmeister, M.; ,
Abstract: CARMENES is a pair of high-resolution ( R ≳ 80, 000) spectrographs covering the wavelength range from 0.52 to 1.71 μm with only small gaps. The instrument has been optimized for precise radial velocity measurements. It was installed and commissioned at the 3.5 m telescope of the Calar Alto observatory in Southern Spain in 2015. The first large science program of CARMENES is a survey of 300 M dwarfs, which started on Jan 1, 2016. We present an overview of the instrument, and provide a few examples of early science results.